2016
DOI: 10.1177/2319510x17701854
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Employer Brand Dimensions on Organisational Commitment: Evidence from Indian IT Industry

Abstract: The purpose of the present research is to explore the relationships between employer branding dimensions and organisational commitment. The reliability and validity of the model has been addressed through confirmatory factor analysis. Structural equation modelling has been used to determine the contribution of employer branding through organisational commitment. The results demonstrate that two dimensions of employer branding, namely development value and social value act as critical predictors of organisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 44 publications
5
19
0
8
Order By: Relevance
“…Also, the results of the SEM analysis show that the employer brand has a positive statistically significant influence on employees loyalty, thus confirming H 2 hypothesis. The results obtained are similar to the results of previous research, which have established a positive link between the employer brand and employees loyalty (Vaijayanthi, Shreenivasan and Roy, 2011;Tanwar, 2017). Satisfaction is included in the research model as a moderator variable.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also, the results of the SEM analysis show that the employer brand has a positive statistically significant influence on employees loyalty, thus confirming H 2 hypothesis. The results obtained are similar to the results of previous research, which have established a positive link between the employer brand and employees loyalty (Vaijayanthi, Shreenivasan and Roy, 2011;Tanwar, 2017). Satisfaction is included in the research model as a moderator variable.…”
Section: Discussionsupporting
confidence: 86%
“…The concept of loyalty to the company has three forms: affective, continuous and normative loyalty. In practice, most attention is paid to affective loyalty, which can be understood as a strong emotional association of the employee with the company due to significant identification and feeling of belonging to it (Tanwar, 2017). According to affective loyalty, the employees identify their own goals and value system with the company's goals, value system and culture, feel a high level of affiliation in the company, which leads to reduced fluctuation, absenteeism, growth of motivation and increased business performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, if the organization is a desirable place to work, employees will enjoy working there which will increase their work performance (Taylor 2010). Most importantly as per Tanwar (2016), the dimensions of employer branding elucidate differences in levels of employees' organizational commitment and through it enterprise can enhance its employee retention levels.…”
Section: Employer Branding and Employee Retentionmentioning
confidence: 99%
“…Addressing the importance of EB, a survey reported that Indian companies have started to recognize the power of EB, where nearly 72% of responding companies consider EB as a top priority (Backhaus, 2016). EB as a human resource tool has been a topic of interest among various researchers, where the power of EB has been researched continuously and has also been evident to significantly impact employees’ interest levels (Matongolo et al, 2018; Tanwar, 2016; Tanwar & Prasad, 2016b).…”
Section: Introductory Backgroundmentioning
confidence: 99%
“…Additionally, it is evident that the strategy of EB has mostly been assessed to directly impact employees’ work-related attitudes and behaviours (Kashyap & Verma, 2018; Rana & Sharma, 2019; Tanwar, 2016; Tanwar & Prasad, 2016b). Although, past studies have made an attempt to integrate the framework of psychological contract (Tanwar & Prasad, 2016a), person-organization fit (Tatar & Ergun, 2018), and job satisfaction (Kaur et al, 2020), Tanwar and Kumar (2019) identified the need to understand the role of social identity theory (SIT) to advance comprehension in the EB literature. SIT argues that EB is likely to affect employees’ identification where a sense of oneness and belongingness for an organization (Ashforth & Mael, 1989) could impact employees’ thoughts of quitting the job (Mael & Ashforth, 1995; Neill & Gaither, 2007; Randsley de Mouraet al, 2009).…”
Section: Introductory Backgroundmentioning
confidence: 99%